Engaging with the Beneficiaries in Reforming Health Care. A Case Study of Patient Involvement in the Reform of Psychiatric Care in the Czech Republic - Karolína Dobiášová; Miriam Kotrusová; Magdalena Wolfová (Transylvanian Review of Administrative Sciences, 2021)
The involvement of patients and their families in healthcare policymaking has been a general trend in recent years. This tendency can be observed also in the process of the current reform of psychiatric care in the Czech Republic, which should gradually shift the focus of psychiatric care from large facilities to community care. Organizations representing patients and their families are among the key stakeholders in this reform. The present study analyses semi-structured in-depth interviews and documents with the objective to map and evaluate the process of patient involvement in the reform from its launch to its implementation in 2012-2019. The study identifies the major barriers to patient involvement – on the part of the patients and their organizations, professionals (healthcare professionals, care providers, administration, policymakers), as well as the whole society. It becomes clear that the reform encourages patient involvement, with a palpable shift from consultation to involvement. Still, there are many obstacles to patient involvement in the Czech Republic: the mental state, social and economic situation of the patients, paternalism on the part of care providers, tokenism or stigmatization of mentally ill people.